Analisis Kemampuan Memproduksi Teks Anekdot dengan Pendekatan Saintifik Siswa Kelas X MAN 1 Bima: Kajian Teks dalam Pembelajaran Bahasa Indonesia Prof. Mahsun, M.Pd - Irwansyah Irwansyah (Center of Language and Cultural Studies, 2019)
This study aims to describe the ability of students at x grade students of MAN 1 Bima in writing anecdotal text with a scientific approach. Therefore to know this problem used the theory of qualitative data analysis and quantitative analysis by using the tabulation width of student learning achievement in the book of Prof. Mahsun, MS, and other theories. The research method used in this research is a qualitative research method with the character of analytic description. Interpretation of data is done through literature method and field observation with student assignment technique writing anecdote text using the scientific approach. Based on the results of data analysis, it can be concluded that the students' ability to analyze at x grade students of MAN 1 Bima in writing anecdotal text with the scientific approach is at less-skilled value, This is evidenced from the results from students’ score that is only under minimum score. This is also evidenced by the results of qualitative data analysis and the score of students is only in the range under the minimum score. it is also evidenced from the results of qualitative data analysis and quantitative data analysis used tabulation data sheet that shows the number of the ability to write anecdote text of all students got to score 30 that is in the less skilled value category.